Neurophysiological underpinnings of balance control and cognitive-motor interaction in early Parkinson’s disease - Manca Peskar; Paolo Manganotti; Uros Marusic; Klaus Gramann (Scientific Reports)
Abstract People with Parkinson’s Disease (PD) often compensate for impaired automatic balance control by engaging additional attentional resources for motor tasks. With disease progression, their cognitive system too becomes increasingly affected, further impairing postural stability. The interaction between cognitive and motor systems in the early disease stages, however, remains poorly investigated. The present study aimed to elucidate behavioral and neurophysiological changes in early-stage PD to identify with greater accuracy the specific disease-related discrepancies from healthy functioning on both cognitive and motor systems. Eighteen participants with PD (aged 62.9 ± 6.6 years) and 18 healthy matched controls (aged 62.9 ± 6.4 years) performed (i) a balancing single task in a semi-tandem stance (ST-sts), (ii) a single visual oddball task with conflicting Stroop color-word stimuli (ST-Stroop), and (iii) a dual-task (DT) combining the two single tasks. Centre of pressure displacement using a force plate and 128-channel electroencephalography (EEG) were recorded. Participants with PD exhibited reduced postural sway compared to controls, and postural sway was lower in DT as opposed to ST. Reduced sway in PD might be attributed to postural rigidity and tonic muscle activation, while in the DT, it might reflect resource conflicts. EEG analyses indicated distinct spectral activity patterns: the central midline low-frequency (δ, θ) power increased with cognitive load, centroparietal β desynchronization intensified with motor load, and parietal α desynchronization heightened during DT in both PD and control groups, underscoring specific frequency bands’ governing roles in cognitive-motor processing. Furthermore, PD participants exhibited heightened or prolonged responses in ERP components related to working memory (frontocentral P2) and conflict resolution (P300), possibly reflecting compensatory neural strategies. Overall, these findings suggest that cognitive capacities, particularly selective attention, might be more affected than sensory acuity in early PD, highlighting areas for targeted interventions.